Analisis Harga Saham Dan Earning Per Share (Eps) Terhadap Bid Ask Spread Pada Saham Syariah Perusahaan Property Dan Real Estate Yang Terdaftar Di ISSI Periode 2014 - 2017 - ANGGRAENI DWI BRILIANTINI, 041311433161 (Departemen Ekonomi Syariah, FEB, Universitas Airlangga, 2019)
This study aims to analyze the effect of stock prices and earnings per share on bid ask spread on sharia shares of property and real estate companies listed in ISSI for the period 2014-2017 both partially and horizontally. This study uses a population of property and real estate companies registered at the ISSI. This study uses a sample of 26 samples of property and real estate companies registered with the ISSI where the sampling technique uses purposive sampling technique. The observation period in this study starts from the period 2014 - 2017. Based on the results of the study, the best estimation model used is the common effect model (CEM), this indicates that the variable share price and earnings per share (EPS) have a significant and simultaneous influence towards bid ask spread of sharia shares of property and real estate companies registered in ISSI for the period 2014 - 2017. The results of the research partially indicate that the stock price variable has a significant negative effect on the bid ask spread of sharia stock property and real estate companies registered in the ISSI period 2014-2017, while the earnings per share (EPS) variable has no influence and is significant towards bid ask spread of sharia shares of property and real estate companies registered in ISSI for the period 2014 - 2017.